2023
DOI: 10.2147/copd.s408325
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Rehabilitation and Chronic Respiratory Diseases: Effects, Mechanisms, and Therapeutic Benefits

Abstract: Chronic respiratory diseases (CRD), is a group of disorders, primarily chronic obstructive pulmonary disease and asthma, which are characterized by high prevalence and disability, recurrent acute exacerbations, and multiple comorbidities, resulting in exercise limitations and reduced health-related quality of life. Exercise training, an important tool in pulmonary rehabilitation, reduces adverse symptoms in patients by relieving respiratory limitations, increasing gas exchange, increasing central and periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 145 publications
0
3
0
Order By: Relevance
“… 54 , 55 Studies have indicated that regular exercise training can ameliorate symptoms of dyspnea and exercise tolerance in patients with COPD. 56 Given that beetroot juice, which is rich in nitrates, has been observed to enhance the exercise capacity of healthy individuals, a number of studies have focused on whether beetroot juice can serve as a dietary therapeutic agent to improve exercise performance and symptoms in patients with COPD. 57 Research by Berry et al found that acute intake of NO3 – rich beetroot juice could prolong the time-to-exhaustion during submaximal constant work rate exercise in patients with COPD without increasing their oxygen consumption.…”
Section: Methodsmentioning
confidence: 99%
“… 54 , 55 Studies have indicated that regular exercise training can ameliorate symptoms of dyspnea and exercise tolerance in patients with COPD. 56 Given that beetroot juice, which is rich in nitrates, has been observed to enhance the exercise capacity of healthy individuals, a number of studies have focused on whether beetroot juice can serve as a dietary therapeutic agent to improve exercise performance and symptoms in patients with COPD. 57 Research by Berry et al found that acute intake of NO3 – rich beetroot juice could prolong the time-to-exhaustion during submaximal constant work rate exercise in patients with COPD without increasing their oxygen consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Exercise training is a widely employed rehabilitation strategy in clinical settings for various conditions, including neurological, musculoskeletal, and respiratory disorders. Current evidence suggests exercise training positively influences pulmonary function in patients with respiratory conditions 11 . For instance, exercise training can enhance cardiorespiratory and motor function in pulmonary fibrosis patients 12 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 Additionally, lifestyle factors like physical inactivity and poor nutrition contribute to the severity of CRDs. 8 , 9 , 10 Epidemiological research suggests that dietary variables, such as antioxidants, may play a vital role in the prevention and management of CRDs. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%